Antibacterial assay of crude extracts from marine sponge Haliclona fascigera in Badi Island of Spermonde Archipelago against shrimp pathogenic bacteria. Issue 1 (May 2021) - Latifah, L A; Tahir, A; Soekamto, N H
Abstract: The marine Sponge Haliclona fascigera, belonging to the genus Haliclona, Family Haliclonidae, Order Haplosclerida, is a source of potentially valuable marine natural products, including diverse bioactive secondary metabolites. These bioactive secondary metabolites could be used as alternative antibiotics for managing pathogenic bacteria in aquaculture. The study aimed to determine the in vitro antibacterial activity of n-hexane, ethyl acetate, and acetone crude extracts against three shrimp pathogenic bacteria and to carry out phytochemical screening. The three crude extracts were produced from H. fascigera collected around Badi Island, Spermonde Archipelago, Indonesia. The crude extracts were screened for their activity against three shrimp pathogenic bacteria: Vibrio harveyi (M-120), Vibrio alginolyticus, and Vibrio parahaemolyticus (T-170). Antibacterial activity assays used the agar diffusion method; the paper discs were impregnated with extract concentrations of 2μg/25μL. Phytochemical screening was carried out using standard protocols to provide supporting data. N-hexane and acetone crude extracts of H. fascigera were able to inhibit Vibrio parahaemolyticus with inhibition zone diameters of 8.07mm and 7.62mm, respectively. The inhibition zone of Ciprofloxacin (positive control) was 10.45 mm. The phytochemical analysis indicated that steroid, terpenoid, and alkaloid compounds were present in H. fascigera . Further studies are needed to reveal the compounds causing the observed antimicrobial effect.